2021
DOI: 10.3389/fonc.2021.663944
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing ERK Pathway Impairs Glycochenodeoxycholate-Mediated Survival and Drug-Resistance in Hepatocellular Carcinoma Cells

Abstract: Glycochenodeoxycholate (GCDA), a toxic component in bile salts, is involved in carcinogenesis of gastrointestinal tumors. The objective of this research was to study the function of ERK1/2 in the GCDA-mediated survival and drug-resistance in hepatocellular carcinoma cells (HCCs). Firstly, extracellular signal-regulated kinase 1/2 (ERK1/2) was detected extensively expressed in liver cancer cells, and silencing ERK1/2 by RNA interference could suppress GCDA-stimulated survival and promote apoptosis. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the pathogenesis of HCC, ERK1, but not ERK2, phosphorylated intestine-specific homeobox, resulting to its nuclear translocation and the expression of downstream genes related to cell proliferation, malignant transformation and the resistance to sorafenib 34 . The expression and activation of MAPK3 were upregulated in HCC tissues and cells 35 , 36 . In line with this, our results indicated that MAPK3 were highly expressed in HCC.…”
Section: Discussionmentioning
confidence: 96%
“…In the pathogenesis of HCC, ERK1, but not ERK2, phosphorylated intestine-specific homeobox, resulting to its nuclear translocation and the expression of downstream genes related to cell proliferation, malignant transformation and the resistance to sorafenib 34 . The expression and activation of MAPK3 were upregulated in HCC tissues and cells 35 , 36 . In line with this, our results indicated that MAPK3 were highly expressed in HCC.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, studies have shown that activation of the p38 pathway can lead to cell cycle arrest and apoptosis [ 212 ]. Activation of JNK can upregulate the expression of pro-apoptotic proteins and activate caspase 3 [ 213 ], while inhibition of ERK can promote cell apoptosis and inhibit the proliferation of tumor cells [ 214 ]. p38 MAPK can be activated by upstream signals involved in the control of various stress responses and DNA damage—for example, cell cycle arrest, mitochondrial damage, and apoptosis [ 215 ].…”
Section: Potential Mechanisms Of Plant-derived Natural Products In Th...mentioning
confidence: 99%